Marine heatwave temperatures enhance larval performance but are meditated by paternal thermal history and inter-individual differences in the purple sea urchin, Strongylocentrotus purpuratus - Leach, Terence S.; Hofmann, Gretchen E. (Frontiers in Physiology, 2023)
Marine heatwave (MHW) events, characterized by periods of anomalous temperature, are an increasingly prevalent threat to coastal marine ecosystems. Given the seasonal phenology of MHWs, the full extent of their biological consequences may depend on how these thermal stress events align with an organism's reproductive cycle. In organisms with more complex life cycles (e.g., many marine invertebrate species) the alignment of adult and larval environments may be an important factor determining offspring success, setting the stage for MHW events to influence reproduction and development in situ. Here, the influence of MHW-like temperatures on the early development of the California purple sea urchin, Strongylocentrotus purpuratus, were explored within the context of paternal thermal history. Based on temperature data collected during MHW events seen in Southern California from 2014-2020, adult urchins were acclimated to either MHW or non-MHW temperatures for 28 days before their sperm was used to produce embryos that were subsequently raised under varying thermal conditions. Once offspring reached an early larval stage, the impact of paternal and offspring environments were assessed on two aspects of offspring performance: larval size and thermal tolerance. Exposure to elevated temperatures during early development resulted in larger, more thermally tolerant larvae, with further influences of paternal identity and thermal history, respectively. The alignment of paternal and offspring exposure to MHW temperatures had additional positive benefits on larval thermal tolerance, but this tolerance significantly decreased when their thermal experience mismatched. As the highest recorded temperatures within past MHW events have occurred during the gametogenesis of many kelp forest benthic marine invertebrate species, such as the purple sea urchin, such parental mediated impacts may represent important drivers of future recruitment and population composition for these species.